2017
DOI: 10.18632/oncotarget.21722
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for predicting the overall and cancer-specific survival of patients with classical Hodgkin lymphoma: a SEER-based study

Abstract: The aim of this study was to establish nomograms, based on significant clinicopathologic parameters, for predicting the overall survival (OS) and the cancer-specific survival (CSS) of patients with classical Hodgkin lymphoma (CHL). The data of 43,330 CHL patients, diagnosed between 1983 and 2014, were obtainedfrom the database of the Surveillance, Epidemiology, and End Results (SEER) program. These patients were randomly divided into training (n = 30,339) and validation (n = 12,991) cohorts. The Kaplan-Meier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In the present study, the mean age of the patients was about 10 years. Epidemiological studies show that HL is less common in children under 5 years of age so that in developing countries it is about 5%, which is consistent with our study (33)(34)(35). In our study, 19 of the patients (54.3%) were male patients, and in general, the prevalence of HL was higher among boys, and at an early age it was reported as high as 3:1, but with increasing age and in adolescents its rate gets equal in both sexes.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean age of the patients was about 10 years. Epidemiological studies show that HL is less common in children under 5 years of age so that in developing countries it is about 5%, which is consistent with our study (33)(34)(35). In our study, 19 of the patients (54.3%) were male patients, and in general, the prevalence of HL was higher among boys, and at an early age it was reported as high as 3:1, but with increasing age and in adolescents its rate gets equal in both sexes.…”
Section: Discussionsupporting
confidence: 93%
“…A study 14 from the British National Lymphoma Investigation involving 6834 HL patients demonstrated that the 5‐ and 10‐year OS increased from 73.5% and 62.4% in the 1970s to 93.8% and 89.6% in the 2000s, with a reduced risk of second malignancy and cardiac‐related deaths over time. A study 15 based on the database of Surveillance, Epidemiology, and End Results (SEER) analyzed 43 330 cHL patients between 1983 and 2014 and found that the 5‐ and 10‐year OS rates were 79.8% and 72.3%, respectively. Similarly, the 5‐year OS of patients with cHL increased by 24% during the past two decades in the present study, which confirmed the benefits for HL from advances in modern treatment techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram, a graphical display of a mathematical model, combines biological and clinical variables for the identification of the probability of clinical events. Compared with the existing tumor staging system, nomograms achieve more excellent prediction precision and prognostic value [2123]. Based on the size of tumor, location, and mitotic index of 127 patients, from 1983 to 2002, the Memorial Sloan Kettering Cancer Center (MSKCC) developed a prognostic nomogram that predicted the risk for tumor recurrence after surgical resection of a localized primary GIST.…”
Section: Discussionmentioning
confidence: 99%